Perspektif Rasio Likuiditas, Rasio Solvabilitas dan Rasio Aktivitas terhadap Profitabilitas Perusahaan pada Sub Sektor Transportasi di Bursa Efek Indonesia - Anggi Tamarina Lubis; Seniwati Sembiring; Ferry Safriandi (Jurnal EBI, 2021)
This study aims to analyze the liquidity ratios, solvency ratios, and activity ratios to the profitability of transportation subsector companies on the Indonesia Stock Exchange for the 2015-2018 period. The data collection method used is the purposive sampling method. This research is a quantitative study. In this study, the population is the transportation sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2018 period. Based on the predetermined criteria, 9 companies were obtained. The analytical method used is multiple linear regression analysis through the F test and t-test to know the effect of the independent variable on the dependent variable. Partially, the current ratio (CR), debt to equity ratio (DER), does not affect profitability, while total assets turnover (tattoo) does not affect profitability. but simultaneously: Current ratio (CR), Debt to equity ratio (DER), and Total assets turn over (TATO) have a significant influence on the company's profitability. Keywords : Current ratio, debt to equity ratio, total assets turn over, and profitability